In Situ/Operando Characterization Techniques to Probe the Electrochemical Reactions for Energy Conversion. Issue 6 (18th April 2018) - Li, Xuning; Wang, Hsin‐Yi; Yang, Hongbin; Cai, Weizheng; Liu, Song; Liu, Bin
Abstract: The water‐splitting reaction, including the hydrogen and oxygen evolution reactions, as well as the electrochemical oxygen and CO2 reduction reactions offer promising solutions to address the global energy scarcity and the associated environmental issues. However, the lack of deep insight into the reaction mechanisms and clear identification of the catalytic active sites hinder any breakthrough for the development of efficient electrocatalysts with high performance and durability. Operando characterization techniques allowing in situ monitoring the surface oxidation state and local atomic‐structure transformation are capable of probing the active sites and promoting the fundamental understanding of the reaction mechanism in these systems. Herein, the recent applications of various operando characterization techniques in identifying the active sites and capturing the geometric structure, oxidation state, and local atomic‐structure evolution of the catalysts during water electrolysis and O2 /CO2 electroreduction are thoroughly summarized. The challenges and outlook in developing operando techniques to further extend the understanding of the underlying mechanism during electrochemical energy‐conversion reactions are discussed. Abstract : Operando characterization techniques allowing in situ monitoring of the local atomic structure transformation are capable of probing active sites and promoting fundamental understanding of reaction mechanisms. The recent applications of various operando characterization techniques in identifying the active sites, capturing the local atomic‐structure evolution of catalysts during various electrochemical catalytic energy conversions are summarized.